Role of Cellular Metabolism in the Formation of Neutrophil Extracellular Traps in Airway Diseases - Morán, Gabriel; Uberti, Benjamín; Quiroga, John (Frontiers in Immunology, 2022)
Neutrophil extracellular traps (NETs) are a recently described mechanism of neutrophils that play an important role in health and disease. NETs are an innate defense mechanism that participate in clearance of pathogens, but they may also cause collateral damage in unrelated host tissues. Neutrophil dysregulation and NETosis occur in multiple lung diseases, such as pathogen-induced acute lung injury, pneumonia, chronic obstructive pulmonary disease (COPD), severe asthma, cystic fibrosis, and recently, the novel coronavirus SARS-CoV-2. More recently, research into immunometabolism has surged due to the possibility of reprogramming metabolism in order to modulate immune functions. The present review analyzes the different metabolic pathways associated with NETs formation, and how these impact on pathologies of the airways.